Colonizing Hawai'i : the cultural power of law - Merry, Sally Engle, 1944-2020. (Princeton, N.J. : Princeton University Press, 2000)
How does law transform family, sexuality, and community in the fractured social world characteristic of the colonizing process? The law was a cornerstone of the so-called civilizing process of nineteenth-century colonialism. It was simultaneously a means of transformation and a marker of the seductive idea of civilization. Sally Engle Merry reveals how, in Hawai'i, indigenous Hawaiian law was displaced by a transplanted Anglo-American law as global movements of capitalism, Christianity, and imperialism swept across the islands. The new law brought novel systems of courts, prisons, and conceptions of discipline and dramatically changed the marriage patterns, work lives, and sexual conduct of the indigenous people of Hawai'i.
A note on language and terminology -- Part 1: Encounters in a contact zone : New England missionaries, lawyers, and the appropriation of Anglo-American law, 1820-1852. The process of legal transformation ; The first transition : religious law ; The second transition : secular law -- Part 2: Local practices of policing and judging in Hilo, Hawai'i. The social history of a planation town ; Judges and caseloads in Hilo ; Protest and the law on the Hilo Sugar Plantation ; Sexuality, marriage, and the management of the body -- Conclusion -- Appendices. A. Cases from Hilo District Court ; B. Accompanying tables.
Includes bibliographical references (pages 349-363) and index.
Print version record.
JSTOR
Keywords: USA -- Government; Hawaiians -- Government relations; Hawaiians -- Legal status, laws, etc; Hawaiians -- Politics and government; Customary law -- Hawaii; United States -- Foreign relations -- Hawaii; Hawaii -- Foreign relations -- United States; États-Unis -- Relations extérieures -- Hawaii; Hawaii -- Relations extérieures -- États-Unis.; Hawaïens -- Relations avec l'État.; Droit coutumier -- Hawaii; 86.06 ethnological jurisprudence; SOCIAL SCIENCE -- Anthropology -- General; Customary law; Hawaiians -- Government relations; Hawaiians -- Legal status, laws, etc; Hawaiians -- Politics and government; Diplomatic relations; Hawaii; United States; Außenpolitik; Geschichte; Kolonialismus; Politik; Rechtssystem; Hawaii; Recht; Rechtsstelsels; Hawaiians -- Government relations; Hawaiians -- Legal status, laws, etc; Hawaiians -- Politics and government; Customary law -- Hawaii; United States -- Foreign relations -- Hawaii; Hawaii -- Foreign relations -- United States; Hawaii; United States of America; Law; Hawaiiens -- Relations avec l'État.; Hawaiiens -- Statut juridique; Hawaiiens -- Politique et gouvernement; Droit coutumier -- États-Unis -- Hawaii; Afghanistan; Baker, James; Blackwell, David; Caucus-race.; Chappaquiddick; Durkheim, Emile; Ford, Gerald; Gephardt, Richard; Hart, Gary; Hodgson, Godfrey; Houston Chronicle; Iran hostage crisis; Jordan, Hamilton; Joslyn, Richard; Kemp, Jack; Kennedy, Robert; Lydon, Christopher; McGovern-Fraser commission; Nevada primary